2016
DOI: 10.1007/s13402-016-0292-6
|View full text |Cite
|
Sign up to set email alerts
|

A network including PU.1, Vav1 and miR-142-3p sustains ATRA-induced differentiation of acute promyelocytic leukemia cells - a short report

Abstract: Our results suggest the existence of a Vav1/PU.1/miR-142-3p network that supports ATRA-induced differentiation in APL-derived cells. Since selective regulation of miRNAs may play a role in the future treatment of hematopoietic malignancies, our results may provide a basis for the development of new therapeutic strategies to restore the expression of miR-142-3p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…It has been reported that VAV1 was expressed in a neuroblastoma cell line SK‐N‐MC and exerted influence on the development of neuroblastomas . A previous study revealed that miR‐142‐3p had negative effects on VAV1 expression, and miR‐142‐3p was important for the agonist‐induced expression of VAV1 and PU.1 . MiR‐499‐5p was reported to be a candidate target of VAV3 and miR‐499‐5p could suppress VAV3 expression in non‐small cell lung cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that VAV1 was expressed in a neuroblastoma cell line SK‐N‐MC and exerted influence on the development of neuroblastomas . A previous study revealed that miR‐142‐3p had negative effects on VAV1 expression, and miR‐142‐3p was important for the agonist‐induced expression of VAV1 and PU.1 . MiR‐499‐5p was reported to be a candidate target of VAV3 and miR‐499‐5p could suppress VAV3 expression in non‐small cell lung cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al indicated that miR-142-3p was a key regulator of normal myeloid differentiation and its reduced expression was related to AML development [37], therefore serving as a candidates for AML prognosis and therapeutic strategy [25]. Grassilli et al demonstrated that the existence of Vav1, PU.1 which regulated ATRA-induced gene expression, as well as miR-142-3p, supported ATRA-induced differentiation in APL-derived NB4 cells [38]. Our study confirmed that miR-142-3p was downregulated in AML PBMC and cells, as well as AML/ATRA and AML/ADR cells.…”
Section: Discussionmentioning
confidence: 99%
“…Micro‐dissected tissues were subjected to RNA extraction with miRNeasy FFPE Kit (QIAGEN), following the manufacturer's protocol. RNA was subjected to real‐time PCR for quantitative measurement of miR‐146a using the TaqMan MicroRNA assay (Life Technologies) and a Bio‐Rad CFX96™ system, as previously reported . Fold‐changes were calculated using the 2 −ΔΔCT method and normalized to the expression of U6 snRNA.…”
Section: Methodsmentioning
confidence: 99%
“…For miR‐146a analysis, RNA was subjected to single stranded cDNA synthesis using a TaqMan MicroRNA Reverse Transcription Kit (Life Technologies), according to the manufacturer's instructions. The cDNAs obtained were employed as templates for quantitative Real‐Time PCR, following a previously described procedure …”
Section: Methodsmentioning
confidence: 99%